Programowanie neurolingwistyczne a zmiany w kompetencjach menedżerskich - Kowalczyk, Elżbieta (NLP and changing in managerial skills, 2005)
In this paper the author has focused on choosing assumption of neuro-linguistic programming (NLP) which helps in implementation changing in the field of managerial skills . The N P theory is one of the most useful tools in the process of professional development in business. In Author 's opinion the most important elements of this conception are : 1) resources, 2) consciousness, 3) outcomes, 4) time, 5) metaprograms, 6) strategies. Each above mentioned points are analyzed in context of obtaining new competences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 498-504